Ecstatic Hymns: The Hymn’s Role in Encountering Mystery in Liturgical Worship - Heeder, Megan (Lumen et Vita, 2018)
The Mass’s music enables us to encounter God by being drawn out of ourselves by beauty. Thus, hymns form us ecstatically by engaging the intellectual, physical, and spiritual elements of our human nature to better know and love God as Mystery and Beauty Engaging the whole human person, singing enables us to offer God all of ourselves and so encounter God as Mystery. Drawing on the work of Hans Urs von Balthasar writes, this paper will reflect on how the beauty of song invites us into the Mystery of Beauty: God. Singing a hymn of praise is a transformative experience of beauty, which draws us out of ourselves, placing us in a posture in which we can encounter and be formed by God, and so more fully be able to encounter God, others, and ourselves.